While my pretty one sleeps : a novel - Clark, Mary Higgins; Clark, Mary Higgins (New York : Simon and Schuster, 1989)
Ethel Lambston, a gossip writer whose forthcoming book threatens to expose leading figures in the fashion World is murdered, and boutique-owner Neeve Kearny becomes intimately involved in the investigation
Keywords: Clothing trade -- Fiction; Women authors -- Fiction; Detective and mystery stories; New York (N.Y.) -- Fiction; Mystery fiction